Two-Party Quantum Private Comparison Protocol Based on Rotational Encryption - Min Hou; Yue Wu (Applied Sciences)
In this paper, we introduce a two-party quantum private comparison (QPC) protocol that employs single photons as quantum resources and utilizes rotational encryption to safeguard the privacy of the inputs. This protocol enables two parties to compare their private data without disclosing any information beyond the outcome of the comparison. The participants’ private data are encoded as single photons, which are encrypted using a rotational encryption method. These encrypted single photons are then transmitted to a semi-honest third party (TP), who conducts single-particle measurements to determine if the users’ private data are equal and subsequently announces the results to the participants. By harnessing the principles of quantum mechanics, we ensure robust protection against potential eavesdropping and participant attacks. In contrast to numerous existing QPC protocols that rely on multi-qubit or d-dimensional quantum states, our method exhibits superior efficiency and practicality. Specifically, our protocol achieves a qubit efficiency of 50% by using two single photons to compare one bit of classical information, and single photons are easier to prepare than multi-qubit and d-dimensional quantum states.